Apnea during Cheyne‐Stokes‐like breathing detected by a piezoelectric sensor for screening of sleep disordered breathing. Issue 1 (2nd December 2014) - Koyama, Takashi; Sato, Shinichi; Kanbayashi, Takashi; Kondo, Hideaki; Watanabe, Hiroyuki; Nishino, Seiji; Shimizu, Tetsuo; Ito, Hiroshi; Ono, Kyoichi
Abstract A simplified diagnostic/monitoring instrument for use in primary screening for sleep‐disordered breathing (SDB) has been desired. This study was designed to assess the validity of a newly developed piezoelectric sensor as a simple and noninvasive tool for primary screening for sleep‐disordered breathing. Forty‐three consecutive patients suspected of having sleep‐disordered breathing and 10 healthy volunteers were enrolled. Breathing movement was detected with the piezoelectric sensor (180 × 30 × 1 mm), which was placed under a bed sheet under patients, and simultaneous polysomnographic recordings were obtained. We counted the number of apneas of >10 s, irrespective of central or obstructive, that appeared during Cheyne‐Stokes‐like breathing with a waxing and waning pattern with an amplitude ratio of >10 in the piezoelectric sensor signal. The correlation coefficient between the number of apneas and apnea–hypopnea index (AHI) was 0.74 (P < 0.0001). The sensitivity/specificity of the number of apneas for distinguishing non‐SDB patients from mild SDB patients (AHI ≥ 5) were 92.1/60.0% and those for separating moderate to severe (AHI ≥ 15) and severe (AHI ≥ 30) SDB patients from the other patients were 96.9/100% and 93.8/86.5%, respectively. There were no complaints from patients about the use of the piezoelectric sensor. The results indicate that the number of apneas detected by this piezoelectric sensor during Cheyne‐Stokes‐like breathing is a potential new index for primary screening for SDB at least for cardiac patients. Thus, the piezoelectric‐sensor system might be useful for simple, noninvasive and comfortable SDB screening at home, hospitals and health care facilities.